The Problem of Assessing the Extent of Somatic Comorbidity in Patients with Major Depressive Disorder and Bipolar Disorder: Metabolic Syndrome, Cardiovascular Diseases, and Type II Diabetes Mellitus - V. E. Makeenko; D. S. Shumskaia; A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
The deleterious impact of depression on the course and outcome of somatic illness is well understood, but the subject of how somatic diseases affect the clinical picture, course, and prognosis of depression has received little attention. There is a lack of awareness on the actual level of comorbidity of somatic diseases in patients with depression, as well as the relationship of comorbidity with clinical features of the disease, patient age, sex, and diagnostic variants of depression. Metabolic syndrome (MS), cardiovascular diseases (CVDs), and type II diabetes (T2D) are the most common comorbidities, causing significant impairment and contributing to mortality rates. All these diseases are closely related to depression through shared pathophysiologic mechanisms of neuro-immuno-metabolic and cardio-metabolic nature. Inflammatory processes and genetic risk factors play a crucial role in realization of these mechanisms. Objective: The aim of this study is to analyze the existent knowledge on prevalence of MS, CVDs, and T2D in patients with major depressive disorder (MDD) and bipolar disorder (BD) in comparative aspect, taking into account possible effects of sex and age. Additionally, we strive to highlight the specific clinical features of comorbid patients. Methods: We conducted a literature review on the topic of comorbidity of MDD and BD with MS, CVDs, and T2D. We mostly selected meta-analyses and prospective studies with large samples. Results: According to current research, MS affects an average of 30-35% of individuals with both BD and MDD, with a minor predominance of male patients. CVDs are detected in an average of 18-20% of patients with BD and 25-45% of patients with MDD, also with a slight predominance of male patients. T2D affects an average of 8-10% of people with both BD and MDD, with no gender differences. There are no consistent and identifiable clinical signs that distinguish comorbid patients from non-comorbid patients for either BD or MDD. Conclusion: More research into the comorbidity of depression and chronic somatic diseases is required, particularly given the scarcity of scientific data for the Russian population.